2019
DOI: 10.1016/j.toxicon.2018.11.432
|View full text |Cite
|
Sign up to set email alerts
|

An examination of microcystin-LR accumulation and toxicity using tethered bilayer lipid membranes (tBLMs)

Abstract: Microcystin-LR (MC-LR) is a potent cyanobacterial toxin responsible for animal and human poisonings worldwide. MC-LR is found in organisms throughout the foodweb, however there is conjecture regarding whether it biomagnifies. Few studies have investigated how MC-LR interacts with lipid membranes, a determinant of biomagnification potential. We tested whether 1 µM MC-LR irreversibly associates with lipid bilayers or causes the creation of pore defects upon short and long-term exposure. Using tethered bilayer li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
1
1
Order By: Relevance
“…The cyanotoxin class of hepatotoxic MC is responsible for animal and human poisoning cases due to bioaccumulation in the liver. This study demonstrated that contrary to the original hypothesis, MC-Leucine Arginine (LR) membrane exposure leads only to small and transient variations in the membrane capacitance, showing that MC-LR is not able to accumulate in cell membranes and modify their integrity (Facey et al 2019).…”
Section: Bacterial Toxin Interaction With Tethered Bilayer Modelscontrasting
confidence: 64%
“…The cyanotoxin class of hepatotoxic MC is responsible for animal and human poisoning cases due to bioaccumulation in the liver. This study demonstrated that contrary to the original hypothesis, MC-Leucine Arginine (LR) membrane exposure leads only to small and transient variations in the membrane capacitance, showing that MC-LR is not able to accumulate in cell membranes and modify their integrity (Facey et al 2019).…”
Section: Bacterial Toxin Interaction With Tethered Bilayer Modelscontrasting
confidence: 64%
“…Cyanotoxin-containing blooms occur throughout the world and are responsible for sporadic episodes of animal illness and death, as well as human poisonings from municipal and recreational water supplies [9,10,11]. Cyanotoxins are highly variable in terms of their molecular structure, production triggers and modes of toxicity [4,11,12]. Effects range from skin irritation to cancer or even fatalities [3,13].…”
Section: Introduction To Cyanobacteria In Freshwater Systemsmentioning
confidence: 99%